CONSTRUÇÃO DO PROTOCOLO DE ENFERMAGEM NA ASSISTÊNCIA À GESTANTE NO PRÉ-NATAL DE BAIXO RISCO - Bertei, Maria Izabel Claus Prato (2024)
The World Health Organization (WHO) aims for a world in which all women and newborns receive quality and equitable care throughout pregnancy, childbirth and the post-natal period. In Brazil, since 1999, the Ministry of Health has been developing public policies to expand the physical network and install equipment to care for pregnancy, the puerperium and the newborn, as well as investing in technical training for health professionals to provide new obstetric care, backed by best practices that encourage and prioritize welcoming pregnant women and their families. In this context, the nursing consultation is an independent activity, exclusive to nurses, and aims to provide conditions for promoting the health of pregnant women and improving their quality of life, through a contextualized and participatory approach. Regulated by the Professional Practice Law No. 94.406/87, nurses can fully monitor low-risk prenatal care in the basic health network. Prenatal care is a programmatic action, carried out in primary care, and is directly related to the health levels of the mother-baby binomial. It is therefore essential to improve and develop these professionals in order to provide comprehensive care to pregnant women. The aim was therefore to develop a nursing protocol for low-risk prenatal care for pregnant women in the municipality of Uruguaiana, in order to further improve the care provided by nurses during prenatal care. The aim was therefore to develop a nursing protocol for low-risk prenatal care in the municipality of Uruguaiana, in order to further improve the care provided by nurses during prenatal care. The methodological approach was descriptive and exploratory, of a quantitative/qualitative nature, using action research. Data was collected in the ESFs located in the central-western region of the municipality of Uruguaiana, from April to August 2023, in a total of seven Health Units. Seven nurses took part in the interview, one from each ESF, and 12 pregnant women. The data from the interviews with nurses and pregnant women was analyzed qualitatively in terms of its content, and the documentary data was analyzed descriptively and quantitatively. The results showed the need to create and implement nursing protocols in nurses' practices during maternal and child health care, to qualify and implement prevention and guidance strategies during the monitoring of pregnant women in the conduct and favorable outcome of prenatal care in egalitarian, universal health practices, developing health education for the dyad, nurses and PHC team in the face of new care guidelines. The nurses surveyed showed an interest in the subject of maternal and child health care, highlighting the need for qualification and public investment in this area. The product and its applicability: the protocol is a support tool for nurses in PHC with pregnant women in low-risk prenatal care. It also supports the continuing education work of these professionals, and qualifies care for pregnant women. It can be replicated in other municipalities and is aligned with care and the reduction of interventions, as well as the improvement of care practices in search of autonomy in nursing care.